Racial integration of multi-ethnic students in Malaysia higher institutions - Abdul Majid, Noraziela; Hassan, Aminuddin; Che Hassan, Norlizah (Human Resource Management Academic Research Society, 2019)
This is a conceptual paper to study the relationship between racial integration and democracy outcomes of multi-ethnic students in Malaysia higher institutions. Malaysia is created of several ethnic groups, every of that has its own culture and heritage such as language, beliefs, customs and more. As such, Malaysians are aware of this and therefore national unity must be nurtured so that the progress of the nation can be built without any hindrance and one of them is through education. However, Malaysian citizens having a distinctly different native language and a distinctive system of early childhood education or better known at the primary school level has left students isolated and out of touch with each other, leading to very limited interactions between different ethnic students and also another issue of concerned is regarding democracy outcomes of these students. Therefore, the general aim of the current study is to identify the racial integration with democracy outcomes among multi-ethnic students in the Institutions of Higher Learning and to examine the mediating effect of social interaction factor between those students. The research will be conducted using quantitative method and going to be supported by open-ended questions as to help the researcher to generate the best research findings. A total of 400 structured questionnaires were distributed through a convenience sampling technique. All the data will be analyzed using the Statistical Package for Social Science (SPSS latest version) program through descriptive and inferential statistics. Pearson Product Coefficient (r) and Structural Equation Modelling (SEM) were applied to answer research questions of this study.